Lithium-ion secondary battery and its manufacturing method

By adding hydroxide particles to the end of the positive electrode current collecting foil of the lithium-ion secondary battery, the decomposed water and HF are used to promote the formation of the AlF3 coating, the problem of corrosion of the positive current collecting foil under high load conditions is solved, and higher corrosion resistance and maintenance of battery performance is achieved.

JP7669336B2Active Publication Date: 2025-04-28PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022202327
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-04-28
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

Under high load conditions, especially during fast charging, the positive current collector foil of the lithium-ion secondary battery is easily corroded, causing aluminum ions (Al) to be released from the corroded surface and accumulate on the negative electrode surface, causing internal short circuits.

Method used

By adding hydroxide (LiOH) particles at the end of the positive electrode current collecting foil, it decomposes and generates water molecules during the charging process, promotes the generation of HF in the non-aqueous electrolyte, and further reacts with the oxide layer of the positive electrode current collecting foil to form a thicker AlF3 coating, thereby improving corrosion resistance.

Benefits of technology

It effectively reduces the release of aluminum ions from the positive electrode current foil under high load conditions during initial use, reduces the risk of internal short circuits, and maintains the efficient discharge capability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669336000003
    Figure 0007669336000003
  • Figure 0007669336000004
    Figure 0007669336000004
  • Figure 0007669336000005
    Figure 0007669336000005
Patent Text Reader

Abstract

To provide a lithium-ion secondary battery and a manufacturing method thereof that can reduce "Al elution from the surface of the positive electrode current collector foil when a high load current is applied in the early stages of use."SOLUTION: A lithium ion secondary battery 1, 101 includes a wound electrode body 50, 150 in which a strip-shaped positive electrode plate 60, 160 and a strip-shaped negative electrode plate 70 are wound in a manner in which a strip-shaped separator 80 is interposed therebetween, a non-aqueous electrolyte 90 containing LiPF6, and a battery case 30 that accommodates them. The positive electrode plate 60, 160 includes a positive electrode current collector foil 61 made of aluminum foil, and a positive electrode active material layer 63, 163 laminated on the surface of the positive electrode current collector foil 61. The surface of current collector foil end portion 61f, 61g of the positive electrode laminate portion 60b, 160b has a larger amount of AlF3 per unit area than the surface of the current collector foil central portion 61h of the positive electrode laminate portion 60b, 160b.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium ion secondary battery and a method for producing the same. [Background technology]

[0002] Patent Document 1 discloses a method for producing a lithium ion secondary battery having a positive electrode plate having a positive electrode active material layer on the surface of a positive electrode current collector foil made of aluminum foil, a negative electrode plate, and a nonaqueous electrolyte solution containing LiPF6. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-60689 A Summary of the Invention [Problem to be solved by the invention]

[0004] In a lithium ion secondary battery having a positive electrode plate having a positive electrode active material layer on the surface of a positive electrode current collector foil made of aluminum foil, a negative electrode plate, and a non-aqueous electrolyte containing LiPF6, when a current with a large load such as rapid charging is applied, a high potential may occur locally in the positive electrode current collector foil. More specifically, in a lithium ion secondary battery having a wound electrode body in which a strip-shaped positive electrode plate and a strip-shaped negative electrode plate are wound in a manner in which a strip-shaped separator is interposed between them, when a current with a large load such as rapid charging is applied, a high potential may occur in the portions of the positive electrode current collector foil included in the positive electrode laminate located at both ends in the axial direction of the wound electrode body (these portions are referred to as the current collector foil ends of the positive electrode laminate). The positive electrode laminate is a portion of the positive electrode plate where a positive electrode active material layer is laminated on the surface of the positive electrode current collector foil.

[0005] Then, when the end of the current collector foil of the positive electrode laminated part, which was at a high potential, corroded, Al (aluminum) was dissolved from the surface of the corroded part, and this was deposited on the surface of the negative electrode, which could cause an internal short circuit. More specifically, in a lithium-ion secondary battery in the early stages of use, a coating of AlF3, which has high corrosion resistance, was not sufficiently formed on the surface of the positive electrode current collector foil, and therefore, the above-mentioned corrosion could cause Al to be dissolved.

[0006] In contrast, in the lithium ion secondary battery of Patent Document 1, LiBF4 and LiFOB are added to the non-aqueous electrolyte as additives that promote the formation of an AlF3 coating on the surface of the positive electrode current collector foil. However, these additives are expensive, and since the formation of the AlF3 coating is insufficient in the initial stage of use, there is a risk of Al elution due to corrosion when a high load current is applied, such as during rapid charging.

[0007] The present invention has been made in consideration of the above-mentioned current situation, and aims to provide a lithium-ion secondary battery capable of reducing "Al elution from the surface of a positive electrode current collector foil when a high load current is applied in the early stages of use," and a method for manufacturing the same. [Means for solving the problem]

[0008] (1) One aspect of the present invention relates to a lithium ion secondary battery including a wound electrode body in which a band-shaped positive electrode plate and a band-shaped negative electrode plate are wound with a band-shaped separator interposed therebetween, a nonaqueous electrolyte containing LiPF6, and a battery case that accommodates these. The positive electrode plate includes a positive electrode current collector foil made of aluminum foil, and a positive electrode active material layer laminated on a surface of the positive electrode current collector foil. A portion of the positive electrode plate where the positive electrode active material layer is laminated on the surface of the positive electrode current collector foil is a positive electrode laminated portion, and a portion of the positive electrode current collector foil included in the positive electrode laminated portion is a portion of the positive electrode current collector foil that is not aligned in an axial direction of the wound electrode body. At least 10% from either endthe portion of the positive current collector foil included in the positive electrode laminate that is located in the center in the axial direction of the wound electrode body is defined as the current collector foil central portion of the positive electrode laminate, the surface of the current collector foil end of the positive electrode laminate is a lithium ion secondary battery in which the amount of AlF3 per unit area is greater than the surface of the current collector foil central portion of the positive electrode laminate.

[0009] In the above-mentioned lithium-ion secondary battery, the surface of the current collector foil end of the positive electrode laminate has a larger amount of AlF3 per unit area than the surface of the current collector foil central part of the positive electrode laminate. Therefore, the surface of the current collector foil end of the positive electrode laminate has a thicker AlF3 coating than the surface of the current collector foil central part of the positive electrode laminate. In such a lithium-ion secondary battery, the surface of the current collector foil end of the positive electrode laminate has higher corrosion resistance than the surface of the current collector foil central part of the positive electrode laminate.

[0010] That is, in the above-mentioned lithium ion secondary battery, the surface of the current collector foil end of the positive electrode laminate of the positive electrode current collector foil included in the positive electrode laminate is selectively made to have high corrosion resistance. The surface of the current collector foil end of the positive electrode laminate of the positive electrode current collector foil included in the positive electrode laminate is a portion that is likely to corrode and cause Al to leach out when a high load current is applied in the early stages of battery use. Therefore, in the above-mentioned lithium ion secondary battery, "Al leach-out from the surface of the positive electrode current collector foil when a high load current is applied in the early stages of use" is reduced.

[0011] However, the discharge capacity of the lithium-ion secondary battery tends to decrease as the amount of AlF3 per unit area on the surface of the positive current collector foil included in the positive electrode laminate increases. For this reason, for example, if the amount of AlF3 per unit area is increased on the entire surface of the positive current collector foil included in the positive electrode laminate in order to increase the corrosion resistance, the discharge capacity of the lithium-ion secondary battery may decrease significantly.

[0012] In contrast, in the above-mentioned lithium ion secondary battery, the amount of AlF3 per unit area is selectively increased in a portion that is easily corroded when a high load current is applied in the early stage of battery use, i.e., the surface of the end of the current collector foil of the positive electrode laminate. This makes it possible to reduce the decrease in the discharge capacity of the lithium ion secondary battery compared to when the amount of AlF3 per unit area is increased over the entire surface of the positive electrode current collector foil included in the positive electrode laminate.

[0013] (2) Another aspect of the present invention is a method for producing the lithium ion secondary battery according to (1) above, comprising: a positive plate preparation step of preparing the positive plate having the positive electrode active material layer on the surface of the positive electrode current collector foil; an electrode body preparation step of preparing the wound electrode body by winding the positive electrode plate and the negative electrode plate with the separator interposed therebetween; a housing step of accommodating the wound electrode body inside the battery case; a liquid injection step of injecting the nonaqueous electrolyte into the battery case containing the wound electrode body to prepare a battery after liquid injection has been completed; and an initial charging step of performing an initial charging of the battery after liquid injection has been completed, wherein in the positive plate preparation step, hydroxide particles are contained in only the end of the positive electrode active material layer that is present on the surface of the end of the current collector foil of the positive electrode laminate.

[0014] In the above-mentioned manufacturing method, in the positive electrode plate manufacturing step, hydroxide particles are contained only in the positive electrode active material layer at the end of the positive electrode active material layer present on the surface of the end of the current collector foil of the positive electrode laminate. In this way, it is possible to manufacture a lithium-ion secondary battery in which "the surface of the end of the current collector foil of the positive electrode laminate has a larger amount of AlF3 per unit area than the surface of the central part of the current collector foil of the positive electrode laminate." This is because the inclusion of hydroxide particles in the positive electrode active material layer makes it easier to form a coating of AlF3 with high corrosion resistance on the surface of the positive electrode current collector foil.

[0015] Specifically, during the period from when a non-aqueous electrolyte is injected into a battery case containing a positive plate, etc., until the battery is completed and ready to be shipped, the AlF3 coating reaction is promoted on the surface of the positive current collector foil in the portion of the positive plate that contains hydroxide particles. In particular, the AlF3 coating reaction is promoted during the initial charging process. Therefore, according to the above-mentioned manufacturing method, a lithium-ion secondary battery can be obtained in which "the surface of the end portion of the current collector foil of the positive electrode laminate has a greater amount of AlF3 per unit area than the surface of the central portion of the current collector foil of the positive electrode laminate."

[0016] As described above, the surface of the end of the current collector foil of the positive electrode laminate in the positive electrode current collector foil included in the positive electrode laminate is a portion that is likely to corrode and cause Al to leach out when a high load current is applied in the early stages of battery use. Therefore, according to the above-mentioned manufacturing method, it is possible to manufacture a lithium-ion secondary battery in which "Al leach-out from the surface of the positive electrode current collector foil when a high load current is applied in the early stages of use" is reduced.

[0017] When LiOH particles are used as the hydroxide particles contained in the positive electrode active material layer end, a highly corrosion-resistant AlF3 coating is formed on the surface of the current collector foil end (aluminum foil) of the positive electrode laminated part by the series of reactions (a) to (c) below. The surface of the positive electrode current collector foil used in the positive electrode plate manufacturing process is covered with an Al2O3 coating, which is an oxide coating.

[0018] (a) LiOH in the edge of the positive electrode active material layer decomposes to generate HO. 2LiOH → Li2O + H2O (Eq. 1) (b) The generated H2O reacts with LiPF6 in the non-aqueous electrolyte to produce HF. LiPF6+H2O→LiF+POF3+2HF (Formula 2) (c) The generated HF reacts with the Al2O3 coating on the surface of the end of the current collecting foil of the positive electrode laminate, generating an AlF3 coating on the surface of the end of the current collecting foil of the positive electrode laminate. Al2O3+6HF→2AlF3+3H2O (Formula 3)

[0019] Even when hydroxide particles other than LiOH particles are used as the hydroxide particles contained in the end of the positive electrode active material layer, the hydroxide particles decompose in the end of the positive electrode active material layer to generate H2O, which causes the reactions of the above formulas 2 and 3, and produces an AlF3 coating on the surface of the current collector foil end of the positive electrode laminate.

[0020] In addition, the ratio of hydroxide particles contained in the positive electrode active material layer end is preferably 0.5 wt% or more of the components contained in the positive electrode active material layer end excluding the hydroxide particles, because this makes it easier for an AlF3 coating to be formed on the surface of the current collector foil end of the positive electrode laminate, and prevents Al elution from occurring from the surface of the current collector foil end of the positive electrode laminate.

[0021] (3) Furthermore, in the method for producing a lithium ion secondary battery according to (2) above, the hydroxide particles may be LiOH particles.

[0022] By using LiOH particles as hydroxide particles contained in the end of the positive electrode active material layer, as described above, the AlF3 coating formation reaction on the surface of the end of the current collector foil of the positive electrode laminate is promoted during the manufacturing process of the battery. Therefore, even if a high load current is applied in the early stage of use of the battery, the occurrence of Al elution from the surface of the end of the current collector foil of the positive electrode laminate can be reduced. In addition, the decomposition of LiOH contained in the end of the positive electrode active material layer generates Li, which is useful for lithium ion secondary batteries, which is preferable.

[0023] (4) Also, another aspect of the present invention is a method for producing a lithium ion secondary battery according to (1), comprising the steps of: a positive electrode plate preparation step of preparing the positive electrode plate having the positive electrode active material layer on the surface of the positive electrode current collector foil; an electrode body preparation step of preparing the wound electrode body by winding the positive electrode plate and the negative electrode plate with the separator interposed therebetween; an accommodation step of accommodating the wound electrode body inside the battery case; a liquid injection step of injecting the nonaqueous electrolyte into the battery case containing the wound electrode body to prepare a liquid injection-completed battery; and an initial charging step of initially charging a finished battery, wherein the liquid injection step injects the nonaqueous electrolyte into the battery case that contains the wound electrode body, the wound electrode body being such that the moisture content of the positive electrode active material layer end portion present on the surface of the current collector foil end portion of the positive electrode laminated portion of the positive electrode active material layer is 100 ppm or more, and the moisture content of the positive electrode active material layer central portion present on the surface of the current collector foil central portion of the positive electrode laminated portion of the positive electrode active material layer is less than the moisture content of the positive electrode active material layer end portion.

[0024] In the above-described manufacturing method, in the liquid injection step, a nonaqueous electrolyte is injected into a battery case housing a wound electrode body that satisfies the following two conditions (d) and (e): (d) the moisture content (moisture content) of the positive electrode active material layer end portion present on the surface of the current collector foil end portion of the positive electrode laminate is 100 ppm or more; (e) the moisture content (moisture content) of the positive electrode active material layer central portion present on the surface of the current collector foil central portion of the positive electrode laminate is lower than the moisture content of the positive electrode active material layer end portion.

[0025] In this way, a lithium ion secondary battery can be manufactured in which "the surface of the end of the current collector foil of the positive electrode laminate has a larger amount of AlF3 per unit area than the surface of the central part of the current collector foil of the positive electrode laminate". The more moisture content of the positive electrode active material layer is increased during the liquid injection process, the more easily a coating of AlF3 having high corrosion resistance is formed on the surface of the positive electrode current collector foil between the injection of the electrolyte into the battery case and the shipment of the battery. In particular, by performing the liquid injection process in a state in which the moisture content of the positive electrode active material layer is 100 ppm or more, a coating of AlF3 having high corrosion resistance is more easily formed on the surface of the positive electrode current collector foil between the injection of the electrolyte into the battery case and the shipment of the battery. In detail, in the initial charging process, the coating generation reaction of AlF3 is promoted, and the corrosion resistance of the surface of the positive electrode current collector foil is increased. Note that in the conventional manufacturing method, the positive electrode active material layer is manufactured so that the moisture content is as small as possible, and the moisture content of the positive electrode active material layer is much less than 100 ppm.

[0026] Therefore, according to the above-mentioned manufacturing method, it is possible to obtain a lithium-ion secondary battery in which "the surface of the end of the current collector foil of the positive electrode laminate has a larger amount of AlF3 per unit area than the surface of the central part of the current collector foil of the positive electrode laminate." As described above, the surface of the end of the current collector foil of the positive electrode laminate of the positive electrode current collector foil included in the positive electrode laminate is a portion that is likely to corrode and cause Al to dissolve when a high load current is applied in the early stages of battery use. Therefore, according to the above-mentioned manufacturing method, it is possible to manufacture a lithium-ion secondary battery in which "Al dissolution from the surface of the positive electrode current collector foil when a high load current is applied in the early stages of use" is reduced.

[0027] In the above-mentioned manufacturing method, a highly corrosion-resistant AlF3 coating is formed on the surface of the positive current collector foil (aluminum foil) by a series of reactions (f) to (g) below. The surface of the positive current collector foil used in the positive plate manufacturing process is coated with an Al2O3 coating, which is an oxide coating. Therefore, the surface of the positive current collector foil included in the wound electrode body used in the liquid injection process is also coated with an Al2O3 coating. (f) After the electrolyte is injected into the battery case in the electrolyte injection process, the H2O contained in the positive electrode plate in the battery case reacts with the LiPF6 in the electrolyte to generate HF. LiPF6+H2O→LiF+POF3+2HF (Formula 4) (g) The generated HF reacts with the Al2O3 coating on the surface of the positive current collector foil, producing an AlF3 coating on the surface of the positive current collector foil. Al2O3+6HF→2AlF3+3H2O (formula 5)

[0028] (5) Furthermore, the method for producing a lithium ion secondary battery according to (4) may further include a moisture content adjustment step between the storing step and the liquid pouring step, in which the moisture content of the end portion of the positive electrode active material layer is adjusted to a value within a range of 100 ppm or more and less than 290 ppm, and the moisture content of a central portion of the positive electrode active material layer is adjusted to a value less than the moisture content of the end portion of the positive electrode active material layer.

[0029] The more the moisture content of the positive electrode active material layer is when the liquid injection process is performed, the more easily an AlF3 coating is formed on the surface of the positive electrode current collector foil, and the more the corrosion resistance of the surface of the positive electrode current collector foil can be improved. However, if the moisture content of the positive electrode active material layer is too high, the discharge capacity of the lithium ion secondary battery decreases. Specifically, if the moisture content of the positive electrode active material layer is 290 ppm or more, the decrease in the discharge capacity of the lithium ion secondary battery increases. Therefore, it is preferable that the moisture content of the positive electrode active material layer when the liquid injection process is performed is within a range of 100 ppm or more and less than 290 ppm.

[0030] In contrast, the above-mentioned manufacturing method includes the following moisture content adjusting step between the accommodation step and the liquid injection step. Specifically, in the moisture content adjusting step, the moisture content of the end of the positive electrode active material layer is adjusted to a value within a range of 100 ppm or more and less than 290 ppm, and the moisture content of the central part of the positive electrode active material layer is adjusted to a state in which it is less than the moisture content of the end of the positive electrode active material layer. As a result, in the liquid injection step, a nonaqueous electrolyte can be injected into a battery case that accommodates a wound electrode body that satisfies the following two conditions (h) and (i). (h) The moisture content of the end of the positive electrode active material layer is within a range of 100 ppm or more and less than 290 ppm. (i) The moisture content of the central part of the positive electrode active material layer is less than the moisture content of the end of the positive electrode active material layer. By manufacturing a lithium ion secondary battery in this manner, it is possible to reduce "Al elution from the surface of the positive electrode current collector foil when a high load current is applied in the early stage of use of the battery" and also to suppress a decrease in the discharge capacity of the battery. [Brief description of the drawings]

[0031] [Figure 1] FIG. 1 is a plan view of a lithium ion secondary battery according to an embodiment and a modified embodiment. [Diagram 2] FIG. 2 is a front view of the lithium-ion secondary battery. [Diagram 3] FIG. 2 is a plan view of a positive electrode plate of the lithium ion secondary battery. [Figure 4] FIG. 4 is a cross-sectional view of the positive electrode plate according to the embodiment, and is a cross-sectional view taken along line BB in FIG. [Diagram 5] FIG. [Figure 6] 6 is a cross-sectional view of the negative electrode plate, taken along line CC in FIG. 5. [Figure 7] FIG. [Figure 8] 2 is a flowchart showing a flow of a method for manufacturing a lithium ion secondary battery according to the embodiment. [Figure 9] 1A to 1C are diagrams illustrating a method for manufacturing a lithium ion secondary battery. [Figure 10] 4 is a cross-sectional view of a positive electrode plate according to a modified embodiment, taken along line BB of FIG. 3. [Figure 11]10 is a flowchart showing a flow of a manufacturing method for a lithium ion secondary battery according to a modified embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] <Embodiment> Next, an embodiment of the present invention will be described. The lithium ion secondary battery 1 (hereinafter also referred to as battery 1) of this embodiment includes a battery case 30, a wound electrode assembly 50 housed inside the battery case 30, a positive electrode terminal member 41, and a negative electrode terminal member 45 (see Figs. 1 and 2). The battery case 30 is a hard case made of metal, and has a rectangular box shape. The battery case 30 includes a metallic case body 21 having a rectangular, bottomed cylindrical shape, and a metallic lid body 11 having a rectangular, flat plate shape that closes the opening of the case body 21 (see Figs. 1 and 2).

[0033] Two rectangular cylindrical through holes (a first through hole and a second through hole, not shown) are formed in the lid body 11. A positive electrode terminal member 41 is inserted into the first through hole, and a negative electrode terminal member 45 is inserted into the second through hole (see FIGS. 1 and 2). Note that cylindrical insulating members (not shown) are interposed between the inner peripheral surface of the first through hole of the lid body 11 and the outer peripheral surface of the positive electrode terminal member 41, and between the inner peripheral surface of the second through hole of the lid body 11 and the outer peripheral surface of the negative electrode terminal member 45.

[0034] The wound electrode body 50 includes a strip-shaped positive electrode plate 60, a strip-shaped negative electrode plate 70, and a strip-shaped separator 80, and is wound in such a manner that the positive electrode plate 60 and the negative electrode plate 70 are interposed with the separator 80 therebetween (see FIG. 7). A nonaqueous electrolyte 90 is contained inside the wound electrode body 50 (see FIG. 2). The nonaqueous electrolyte 90 is also contained on the bottom side inside the battery case 30. The positive electrode plate 60 of the wound electrode body 50 is connected to a positive electrode terminal member 41 inside the battery case 30. The negative electrode plate 70 is connected to a negative electrode terminal member 45 inside the battery case 30.

[0035] The positive electrode plate 60 has a belt shape extending in the longitudinal direction DL, and includes a positive electrode current collector foil 61 made of aluminum foil, and a positive electrode active material layer 63 laminated on the surfaces (first surface 61b and second surface 61c) of the positive electrode current collector foil 61 (see Figs. 3 and 4). The positive electrode active material layer 63 contains positive electrode active material particles 64, a binder 65, and a conductive material 66. In this embodiment, the positive electrode active material particles 64 are lithium transition metal composite oxide particles, specifically, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2 particles are used. PVDF is used as the binder 65. Acetylene black is used as the conductive material 66.

[0036] The positive electrode plate 60 has a positive electrode laminated portion 60b and a positive electrode non-laminated portion 60c (see Figs. 3 and 4). The positive electrode laminated portion 60b and the positive electrode non-laminated portion 60c are adjacent to each other in the width direction DW of the positive electrode plate 60. The width direction DW is a direction perpendicular to the longitudinal direction DL. The positive electrode laminated portion 60b is a portion of the positive electrode plate 60 where the positive electrode active material layer 63 is laminated on the surface (first surface 61b and second surface 61c) of the positive electrode current collector foil 61. On the other hand, the positive electrode non-laminated portion 60c is a portion of the positive electrode plate 60 where the positive electrode active material layer 63 is not laminated on the surface (first surface 61b and second surface 61c) of the positive electrode current collector foil 61, and is a portion consisting of only the positive electrode current collector foil 61.

[0037] In addition, the positive electrode current collector foil 61 included in the positive electrode laminated portion 60b has portions located at both ends in the axial direction DX of the wound electrode body 50, which are referred to as current collector foil ends 61f, 61g of the positive electrode laminated portion 60b (see FIG. 4). In addition, the positive electrode current collector foil 61 included in the positive electrode laminated portion 60b has a portion located at the center in the axial direction DX of the wound electrode body 50, which is referred to as current collector foil center portion 61h of the positive electrode laminated portion 60b. The width direction DW of the positive electrode plate 60 coincides with the axial direction DX of the wound electrode body 50 (see FIG. 7). Therefore, the current collector foil ends 61f, 61g of the positive electrode laminated portion 60b are located at both ends of the positive electrode laminated portion 60b in the width direction DW. On the other hand, the current collector foil center portion 61h of the positive electrode laminated portion 60b is located at the center of the positive electrode laminated portion 60b in the width direction DW.

[0038] The negative electrode plate 70 has a belt shape extending in the longitudinal direction DL, and includes a negative electrode current collector foil 71 made of copper foil, and a negative electrode active material layer 73 laminated on the surfaces (first surface 71b and second surface 71c) of the negative electrode current collector foil 71 (see FIGS. 5 and 6). The negative electrode active material layer 73 contains negative electrode active material particles 74 and a binder 75. In this embodiment, graphite particles are used as the negative electrode active material particles 74. Also, CMC (carboxymethyl cellulose) and SBR (styrene butadiene rubber) are used as the binder 75.

[0039] The negative electrode plate 70 has a negative electrode laminated portion 70b and a negative electrode non-laminated portion 70c (see Figs. 5 and 6). The negative electrode laminated portion 70b and the negative electrode non-laminated portion 70c are adjacent to each other in the width direction DW of the negative electrode plate 70. The width direction DW is a direction perpendicular to the longitudinal direction DL. The negative electrode laminated portion 70b is a portion of the negative electrode plate 70 where the negative electrode active material layer 73 is laminated on the surface (first surface 71b and second surface 71c) of the negative electrode current collector foil 71. On the other hand, the negative electrode non-laminated portion 70c is a portion of the negative electrode plate 70 where the negative electrode active material layer 73 is not laminated on the surface (first surface 71b and second surface 71c) of the negative electrode current collector foil 71, and is a portion consisting of only the negative electrode current collector foil 71.

[0040] The separator 80 has a porous resin sheet and a heat-resistant layer made of heat-resistant particles formed on the surface of the porous resin sheet. In this embodiment, a three-layer structure porous resin sheet in which a porous polyethylene layer is interposed between two porous polypropylene layers is used as the porous resin sheet. The nonaqueous electrolyte 90 contains an organic solvent (specifically, ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate) and LiPF6. In the wound electrode body 50, the positive electrode plate 60, the negative electrode plate 70, and the separator 80 are wound in such a manner that the positive electrode laminated portion 60b of the positive electrode plate 60 overlaps the negative electrode laminated portion 70b of the negative electrode plate 70 in the thickness direction DT via the separator 80 (see FIG. 7).

[0041] In the positive electrode plate 60 of this embodiment, the surfaces (first surface 61b and second surface 61c) of the current collector foil ends 61f, 61g of the positive electrode laminate 60b have a larger amount of AlF3 per unit area than the surface (first surface 61b and second surface 61c) of the current collector foil central portion 61h of the positive electrode laminate 60b. Therefore, the surfaces of the current collector foil ends 61f, 61g of the positive electrode laminate 60b have a thicker coating of AlF3 (not shown) than the surface of the current collector foil central portion 61h of the positive electrode laminate 60b. In such a battery 1, the surfaces of the current collector foil ends 61f, 61g of the positive electrode laminate 60b have higher corrosion resistance than the surface of the current collector foil central portion 61h of the positive electrode laminate 60b.

[0042] That is, in the battery 1 of this embodiment, the corrosion resistance is selectively increased for the surface of the current collector foil ends 61f, 61g of the positive electrode laminate 60b among the positive electrode current collector foil 61 included in the positive electrode laminate 60b. The surface of the current collector foil ends 61f, 61g of the positive electrode laminate 60b is a site that is likely to corrode and cause Al to leach out when a high load current is applied in the early stages of use of the battery 1. Therefore, in the battery 1 of this embodiment, "Al leach-out from the surface of the positive electrode current collector foil 61 when a high load current is applied in the early stages of use" is reduced.

[0043] The current collector foil end 61f of the positive electrode laminate 60b is an end (the left end of the positive electrode laminate 60b in FIG. 4) that occupies 10% of the range of the positive electrode current collector foil 61 included in the positive electrode laminate 60b in the width direction DW (i.e., the axial direction DX). That is, the current collector foil end 61f is a portion having a width dimension that is 10% of the width dimension of the positive electrode current collector foil 61 included in the positive electrode laminate 60b. The current collector foil end 61f of the positive electrode laminate 60b (the right end of the positive electrode laminate 60b in FIG. 4) also has a width dimension equivalent to that of the current collector foil end 61f (see FIG. 4). Moreover, the current collector foil central portion 61h of the positive electrode laminate 60b also has a width dimension equivalent to that of the current collector foil end 61f.

[0044] Incidentally, the greater the amount of AlF3 per unit area on the surface of the positive current collector foil 61 included in the positive electrode laminate 60b, the lower the discharge capacity of the battery 1. For this reason, for example, if the amount of AlF3 per unit area is increased on the entire surface of the positive current collector foil 61 included in the positive electrode laminate 60b in order to improve corrosion resistance, there is a risk that the discharge capacity of the lithium ion secondary battery (hereinafter also simply referred to as the battery) will be significantly reduced.

[0045] In contrast, in the battery 1 of this embodiment, the amount of AlF3 per unit area is selectively increased in the portions that are easily corroded when a high load current is applied in the early stage of use of the battery 1, i.e., the surfaces (the first surface 61b and the second surface 61c) of the current collector foil ends 61f, 61g of the positive electrode laminate 60b. This makes it possible to reduce the amount of decrease in the discharge capacity of the lithium ion secondary battery compared to the case where the amount of AlF3 per unit area is increased over the entire surface of the positive electrode current collector foil 61 included in the positive electrode laminate 60b.

[0046] Next, a method for manufacturing the battery 1 according to the embodiment will be described. FIG. 8 is a flowchart showing the flow of the method for manufacturing the battery 1. First, in step S1 (positive electrode plate manufacturing step), a positive electrode plate 60 having a positive electrode active material layer 63 on the surface (first surface 61b and second surface 61c) of a positive electrode current collector foil 61 is manufactured. Specifically, first, a positive electrode active material particle 64, a binder 65, a conductive material 66, and a solvent (not shown) are mixed to manufacture a positive electrode paste 63P. Next, this positive electrode paste 63P is applied to the first surface 61b of the strip-shaped positive electrode current collector foil 61 (more specifically, a portion of the positive electrode current collector foil 61 excluding the positive electrode non-laminated portion 60c) to form a positive electrode paste layer 68 (see FIG. 4). In FIG. 4, the reference numerals of the portions related to the positive electrode paste layer 68 are indicated in parentheses.

[0047] Next, a plurality of hydroxide particles 67 are contained in both ends 68f, 68g of the positive electrode paste layer 68. For example, a powder (or a mixture of the powder and a solvent) consisting of a plurality of hydroxide particles 67 is applied to the surfaces of both ends 68f, 68g of the positive electrode paste layer 68. The end 68f of the positive electrode paste layer 68 is an end (left end in FIG. 4) that occupies 10% of the range of the positive electrode paste layer 68 in the width direction DW (i.e., the axial direction DX). That is, the end 68f of the positive electrode paste layer 68 is a portion having a width dimension that is 10% of the width dimension of the positive electrode paste layer 68. The end 68g (right end in FIG. 4) of the positive electrode paste layer 68 also has a width dimension equivalent to that of the end 68f (see FIG. 4). In this embodiment, LiOH particles are used as the hydroxide particles 67.

[0048] Next, the positive electrode paste layer 68 on the first surface 61b of the positive electrode current collector foil 61 is dried. As a result, the solvent is evaporated from the positive electrode paste layer 68, and the positive electrode active material layer 63 is formed on the first surface 61b of the positive electrode current collector foil 61 (see FIG. 4). In the positive electrode active material layer 63 thus formed, the hydroxide particles 67 are contained only in the positive electrode active material layer ends 63f, 63g, which are both ends of the positive electrode active material layer, and the hydroxide particles 67 are not contained in the other portions. In the same manner, the positive electrode active material layer 63 is also formed on the second surface 61c of the positive electrode current collector foil 61, and the positive electrode plate 60 consisting of the positive electrode laminated portion 60b and the positive electrode non-laminated portion 60c is produced (see FIG. 4). Note that, in the positive electrode active material layer 63 on the second surface 61c, the hydroxide particles 67 are also contained only in the positive electrode active material layer ends 63f, 63g, which are both ends of the positive electrode active material layer, and the hydroxide particles 67 are not contained in the other portions.

[0049] As described above, in the positive electrode plate fabrication step of this embodiment, the hydroxide particles 67 are contained only in the positive electrode active material layer ends 63f, 63g present on the surfaces (first surface 61b and second surface 61c) of the current collector foil ends 61f, 61g of the positive electrode laminated portion 60b of the positive electrode active material layer 63. The positive electrode active material layer ends 63f, 63g are ends that occupy 10% of the range of the positive electrode active material layer 63 in the width direction DW (i.e., the axial direction DX). The first surface 61b and the second surface 61c of the positive electrode current collector foil 61 (aluminum foil) provided in step S2 (positive electrode plate fabrication step) are covered with an Al2O3 coating, which is an oxide coating.

[0050] Then, in step S2 (electrode body fabrication process), the positive electrode plate 60, the negative electrode plate 70, and the separator 80 are wound together in such a manner that the separator 80 is interposed between the positive electrode plate 60 and the negative electrode plate 70, to fabricate the wound electrode body 50 (see FIG. 7).

[0051] Next, in step S3 (accommodating step), the wound electrode body 50 is accommodated inside the battery case 30. Specifically, first, the lid body 11 is prepared, and the positive electrode terminal member 41 and the negative electrode terminal member 45 are assembled to the lid body 11. Thereafter, the positive electrode terminal member 41 assembled to the lid body 11 is connected to the positive electrode plate 60 included in the wound electrode body 50. Specifically, the positive electrode terminal member 41 is welded to the positive electrode non-laminated portion 60c of the positive electrode plate 60 included in the wound electrode body 50. Furthermore, the negative electrode terminal member 45 assembled to the lid body 11 is connected to the negative electrode plate 70 included in the wound electrode body 50. Specifically, the negative electrode terminal member 45 is welded to the negative electrode non-laminated portion 70c of the negative electrode plate 70 included in the wound electrode body 50. As a result, the lid 11 and the wound electrode body 50 are integrated via the positive electrode terminal member 41 and the negative electrode terminal member 45 .

[0052] Next, the wound electrode body 50 integrated with the lid body 11 is housed inside the case body 21, and the opening of the case body 21 is closed by the lid body 11. In this state, the lid body 11 and the case body 21 are welded all around. As a result, the case body 21 and the lid body 11 are joined to form a battery case 30, and an assembled battery 1A is produced (see FIG. 9). The assembled battery 1A is a structure in which the battery case 30, the wound electrode body 50, the positive electrode terminal member 41, and the negative electrode terminal member 45 are assembled. Specifically, the assembled battery 1A includes the battery case 30, the wound electrode body 50 housed inside the battery case 30, and the positive electrode terminal member 41 and the negative electrode terminal member 45 connected to the wound electrode body 50.

[0053] Next, in step S4 (injection step), non-aqueous electrolyte 90 is injected into the battery case 30 housing the wound electrode body 50 to produce a fully-injected battery 1B (see FIG. 9). Specifically, an injection hole (not shown) is formed in the lid 11 of the battery case 30 constituting the fully-assembled battery 1A. The non-aqueous electrolyte 90 is injected into the battery case 30 constituting the fully-assembled battery 1A through this injection hole. This causes the inside of the wound electrode body 50 to be impregnated with the non-aqueous electrolyte 90, and causes the non-aqueous electrolyte 90 to be housed on the bottom side inside the battery case 30. The injection hole is then sealed to produce the fully-injected battery 1B.

[0054] Next, in step S5 (initial charging step), initial charging is performed on the battery 1B after the electrolyte injection is complete. This activates the battery 1B and turns it into a battery 1. In the initial charging step of this embodiment, the battery 1B is charged at a constant current of 0.2 C until the battery voltage of the battery 1B reaches 4.1 V. After that, the battery 1 after the initial charging is inspected, and the battery 1 is completed and ready for shipment.

[0055] In the manufacturing method of the present embodiment, in the positive electrode plate preparation step (step S1), hydroxide particles 67 are contained only in the positive electrode active material layer 63 at the positive electrode active material layer ends 63f, 63g present on the surfaces of the current collector foil ends 61f, 61g of the positive electrode laminate 60b. In this manner, it is possible to manufacture a battery 1 in which the surfaces of the current collector foil ends 61f, 61g of the positive electrode laminate 60b have a larger amount of AlF3 per unit area than the surface of the current collector foil central portion 61h of the positive electrode laminate 60b. This is because the hydroxide particles 67 contained in the positive electrode active material layer 63 makes it easier to form a coating of AlF3 having high corrosion resistance on the surfaces (first surface 61b and second surface 61c) of the positive electrode current collector foil 61.

[0056] Specifically, during the period from when the nonaqueous electrolyte 90 is injected into the battery case 30 housing the wound electrode body 50 having the positive electrode plate 60 and the like until the battery 1 is completed and ready to be shipped, the following series of reactions (a) to (c) occur in the portion of the positive electrode plate 60 containing the hydroxide particles 67, thereby accelerating the AlF3 coating formation reaction on the surface of the positive electrode current collector foil 61. In particular, the AlF3 coating formation reaction is accelerated in the initial charging step (step S5). For this reason, according to the manufacturing method of this embodiment, it is possible to obtain a battery 1 in which "the surface of the current collector foil ends 61f, 61g of the positive electrode laminate 60b has a larger amount of AlF3 per unit area than the surface of the current collector foil central portion 61h of the positive electrode laminate 60b."

[0057] (a) LiOH in the positive electrode active material layer ends 63f and 63g decomposes to generate H2O. 2LiOH→Li2O+H2O (Equation 6) (b) The generated H2O reacts with LiPF6 in the non-aqueous electrolyte 90 to generate HF. LiPF6 + H2O → LiF + POF3 + 2HF (Equation 7) (c) The generated HF reacts with the Al2O3 coating on the surface of the current collector foil ends 61f, 61g of the positive electrode laminate 60b, generating an AlF3 coating on the surface of the current collector foil ends 61f, 61g of the positive electrode laminate 60b. Al2O3 + 6HF → 2AlF3 + 3H2O (Equation 8)

[0058] As described above, the surface of the current collector foil ends 61f, 61g of the positive electrode laminate 60b among the positive electrode current collector foil 61 included in the positive electrode laminate 60b is a portion that is likely to corrode and cause Al to leach out when a high load current is applied in the early stages of battery use. Therefore, according to the manufacturing method of this embodiment, it is possible to manufacture a lithium ion secondary battery 1 in which "Al leach-out from the surface of the positive electrode current collector foil 61 when a high load current is applied in the early stages of use" is reduced.

[0059] <Examples 1 to 5> In Examples 1 to 5, in step S1 (positive electrode plate preparation step), the ratio of the hydroxide particles 67 to the components excluding the hydroxide particles 67 among the components contained in the positive electrode active material layer ends 63f, 63g (hereinafter, this is also simply referred to as the ratio of the hydroxide particles 67) was made different. That is, in Examples 1 to 5, the weight ratio of the components excluding the hydroxide particles 67 to the hydroxide particles 67 among the components contained in the positive electrode active material layer ends 63f, 63g was made different. The batteries 1 of Examples 1 to 5 were prepared in the same manner except for the above. Specifically, in Example 1, the ratio of the hydroxide particles 67 was set to 0.1 wt%. In Example 2, the ratio of the hydroxide particles 67 was set to 0.5 wt%. In Example 3, the ratio of the hydroxide particles 67 was set to 1.0 wt%. In Example 4, the ratio of the hydroxide particles 67 was set to 3.0 wt%. In Example 5, the ratio of the hydroxide particles 67 was set to 5.0 wt%.

[0060] <Comparative Example 1> In Comparative Example 1, the ratio of hydroxide particles 67 was set to 0 wt %. That is, in Comparative Example 1, a positive electrode plate was produced that did not contain hydroxide particles 67. Otherwise, the lithium ion secondary battery of Comparative Example 1 was produced in the same manner as in Example 1.

[0061] <Investigation of the AlF3 coating on the positive electrode current collector foil> Next, the AlF3 coating on the surface of the positive electrode current collector foil was investigated for the batteries of Examples 1 to 5 and Comparative Example 1. All of the batteries investigated were batteries that were completed and ready for shipment, and were unused products (i.e., new products).

[0062] Specifically, each battery was disassembled and the positive electrode plate was taken out. Then, the taken-out positive electrode plate was immersed in ethyl methyl carbonate for 10 minutes, and then dried to remove the components of the nonaqueous electrolyte 90 adhering to the positive electrode plate. Then, the positive electrode active material layer was peeled off from the positive electrode current collector foil 61 of this positive electrode plate to expose the first surface 61b and the second surface 61c of the positive electrode current collector foil 61. Then, the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 were analyzed by SEM-EDX (energy dispersive X-ray spectroscopy) to calculate the ratio of F element to Al element (F / Al). Specifically, the value of (F / Al) was calculated for the current collector foil end portions 61f, 61g and the current collector foil central portion 61h of the positive electrode laminated portion 60b. It can be said that the larger the value of (F / Al), the larger the amount of AlF3 per unit area.

[0063] As a result of the investigation, in the battery of Comparative Example 1, the surfaces of the current collector foil ends 61f, 61g of the positive electrode laminate 60b had the same value of (F / Al) as the surface of the current collector foil central portion 61h of the positive electrode laminate 60b. On the other hand, in the batteries of Examples 1 to 5, the surfaces of the current collector foil ends 61f, 61g of the positive electrode laminate 60b had a larger value of (F / Al) than the surface of the current collector foil central portion 61h of the positive electrode laminate 60b. Therefore, it can be said that the amount of AlF3 per unit area is larger and the thickness of the coating of AlF3 is thicker on the surfaces of the current collector foil ends 61f, 61g of the positive electrode laminate 60b than the surface of the current collector foil central portion 61h of the positive electrode laminate 60b. In such a battery 1, the surfaces of the current collector foil ends 61f, 61g of the positive electrode laminate 60b have higher corrosion resistance than the surface of the current collector foil central portion 61h of the positive electrode laminate 60b.

[0064] More specifically, in Examples 1 to 5, the value of (F / Al) in the current collector foil central portion 61h of the positive electrode laminate portion 60b was equivalent to that in Comparative Example 1, but the value of (F / Al) in the current collector foil ends 61f, 61g of the positive electrode laminate portion 60b was greater than that in Comparative Example 1. From this result, it can be said that by including hydroxide particles 67 in the positive electrode active material layer ends 63f, 63g of the positive electrode active material layer 63, the formation of an AlF3 coating is promoted on the surface of the current collector foil ends 61f, 61g of the positive electrode laminate portion 60b, and the corrosion resistance of the surface of the current collector foil ends 61f, 61g of the positive electrode laminate portion 60b can be improved.

[0065] <High-load current test> Next, a high-load current test was conducted on the batteries of Examples 1 to 5 and Comparative Example 1. Note that all of the batteries used in this test were batteries that had been completed and were ready for shipping, and were unused products (i.e., new products). Therefore, for all of the batteries used in this test, the high-load current applied in this test was the high-load current applied in the early stages of use.

[0066] In this test, 20 charge / discharge cycles were performed for each battery in a temperature environment of 25°C, with the following charge / discharge cycle being considered as one cycle. Specifically, the charge / discharge cycle was as follows: First, discharge at a current value of 0.2C until the battery voltage value reached 3.5V. Then, pause for 10 minutes. Then, charge at a current value of 1C until the battery voltage value reached 4.0V. Then, pause for 10 minutes. With this charge / discharge cycle as one cycle, 20 charge / discharge cycles were performed.

[0067] After performing the above-mentioned charge-discharge cycle for 20 cycles for each battery, the presence or absence of Al elution from the first surface 61b and the second surface 61c of the positive electrode collector foil 61 was investigated. Specifically, after performing 20 charge-discharge cycles, each battery was disassembled to remove the positive electrode plate. Then, the removed positive electrode plate was immersed in ethyl methyl carbonate for 10 minutes, and then dried to remove the components of the nonaqueous electrolyte 90 attached to the positive electrode plate. Then, the positive electrode active material layer was peeled off from the positive electrode collector foil 61 of this positive electrode plate to expose the first surface 61b and the second surface 61c of the positive electrode collector foil 61. Then, the first surface 61b and the second surface 61c of the positive electrode collector foil 61 were observed with a microscope to confirm the presence or absence of pitting corrosion. The pitting corrosion is due to the elution of Al from the first surface 61b and the second surface 61c of the positive electrode collector foil 61. Therefore, the presence or absence of Al elution can be determined by the presence or absence of pitting corrosion. The results are shown in Table 1. In Table 1, "Al pitting corrosion" is described and rated on a three-level scale: good, bad, or incorrect.

[0068] [Table 1]

[0069] As shown in Table 1, in Examples 2 to 5, the evaluation of Al pitting corrosion was ◯, and no pitting corrosion was present on the first surface 61b and the second surface 61c of the positive current collector foil 61. From this result, it can be said that in the batteries 1 of Examples 2 to 5, when a high load current was applied in the early stages of use, it was possible to prevent Al elution from the first surface 61b and the second surface 61c of the positive current collector foil 61. Therefore, it can be said that the batteries 1 of Examples 2 to 5 are batteries in which Al elution from the first surface 61b and the second surface 61c of the positive current collector foil 61 is unlikely to occur when a high load current is applied in the early stages of use.

[0070] On the other hand, in Comparative Example 1, the evaluation of Al pitting corrosion was ×, and many pitting corrosion was present on the first surface 61b and the second surface 61c of the positive current collector foil 61. Specifically, many pitting corrosion was present on the current collector foil ends 61f, 61g of the positive electrode laminated portion 60b. Therefore, it can be said that the battery of Comparative Example 1 is a battery in which Al elution from the first surface 61b and the second surface 61c of the positive current collector foil 61 is likely to occur when a high load current is applied in the early stage of use.

[0071] In Example 1, the evaluation of Al pitting corrosion was Δ, and pitting corrosion was present at the current collector foil ends 61f, 61g of the positive electrode laminated portion 60b, but the number of pitting corrosion was small and the size of the pitting corrosion was small compared to Comparative Example 1. From this result, it can be said that in the battery 1 of Example 1, when a high load current is applied in the early stage of use, the elution of Al from the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 can be reduced compared to the battery of Comparative Example 1. Therefore, it can be said that the elution of Al from the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 is less likely to occur in the battery 1 of Example 1 compared to the battery of Comparative Example 1 when a high load current is applied in the early stage of use.

[0072] <Discharge capacity measurement test> In addition, the discharge capacity was measured for the batteries of Examples 1 to 5 and Comparative Example 1. Specifically, first, each battery was charged at a current value of 0.2C until the battery voltage value reached 4.2V. Then, charging was performed while maintaining the battery voltage value at 4.2V, to bring the SOC to 100%. Then, discharging was performed at a current value of 0.2C until the battery voltage value reached 3.0V. Then, discharging was performed while maintaining the battery voltage value at 3.0V, to bring the SOC to 0%. At this time, the amount of discharged electricity from SOC 100% to SOC 0% was measured as the discharge capacity of each battery. Then, the magnitude of the discharge capacity of each battery was evaluated. The results are shown in Table 1.

[0073] As indicated by circles in Table 1, the batteries of Examples 1 to 5 and Comparative Example 1 were able to obtain sufficient discharge capacity. Specifically, the battery of Comparative Example 1 had the largest discharge capacity, and the higher the ratio (wt%) of hydroxide particles 67 (specifically, LiOH) was, the smaller the discharge capacity of the battery produced. In particular, the discharge capacity of the batteries of Examples 1 to 5 was smaller than that of the battery of Comparative Example 1, but the amount of decrease was small.

[0074] From the above test results, it can be said that by including the hydroxide particles 67 in the positive electrode active material layer ends 63f, 63g, it is possible to reduce Al elution from the positive electrode current collector foil 61. Furthermore, it can be said that the ratio of the hydroxide particles 67 to the components excluding the hydroxide particles 67 among the components contained in the positive electrode active material layer ends 63f, 63g is more preferably 0.5 wt % or more. This is because it becomes easier for an AlF3 coating to be formed on the surface of the current collector foil ends 61f, 61g of the positive electrode laminate 60b, and it is possible to prevent the occurrence of Al elution from the surface of the current collector foil ends 61f, 61g of the positive electrode laminate 60b.

[0075] <Transformation> Next, a modified embodiment of the present invention will be described. Here, differences from the embodiment will be mainly described, and similarities to the embodiment will be omitted or simplified. A lithium ion secondary battery 101 (hereinafter also referred to as battery 101) of this modified embodiment is different from the battery 1 of the embodiment only in the positive electrode plate 160 constituting the wound electrode body 150, and is otherwise the same (see Figs. 1 and 2). The positive electrode plate 160 is different from the positive electrode plate 60 of the embodiment only in the positive electrode active material layer 163, and is otherwise the same. The positive electrode active material layer 163 is different from the positive electrode plate 60 of the embodiment in that it does not contain hydroxide particles 67. This positive electrode plate 160 also has a positive electrode laminated portion 160b and a positive electrode non-laminated portion 160c, like the positive electrode plate 60 of the embodiment (see Figs. 3 and 10).

[0076] In the positive electrode plate 160 of this modified embodiment, the surfaces (first surface 61b and second surface 61c) of the current collector foil ends 61f, 61g of the positive electrode laminate 160b have a larger amount of AlF3 per unit area than the surface (first surface 61b and second surface 61c) of the current collector foil central portion 61h of the positive electrode laminate 160b. Therefore, the surfaces of the current collector foil ends 61f, 61g of the positive electrode laminate 160b have a thicker coating of AlF3 (not shown) than the surface of the current collector foil central portion 61h of the positive electrode laminate 160b. Therefore, the surfaces of the current collector foil ends 61f, 61g of the positive electrode laminate 160b have higher corrosion resistance than the surface of the current collector foil central portion 61h of the positive electrode laminate 160b. Therefore, in the battery 101 of this modified embodiment, "Al elution from the surface of the positive electrode current collector foil 61 when a high load current is applied in the early stage of use" is reduced.

[0077] As described above, in the battery 101 of this modified embodiment, the amount of AlF3 per unit area is selectively increased in the portions that are easily corroded when a high load current is applied in the early stages of use of the battery 101, i.e., the surfaces of the current collector foil ends 61f, 61g of the positive electrode laminate 160b. This makes it possible to reduce the amount of decrease in the discharge capacity of the battery compared to the case where the amount of AlF3 per unit area is increased over the entire surface of the positive electrode current collector foil 61 included in the positive electrode laminate 160b.

[0078] Next, a manufacturing method of the battery 101 according to the modified embodiment will be described. FIG. 11 is a flowchart showing the flow of the manufacturing method of the battery 101. First, in step T1 (positive electrode plate manufacturing step), a positive electrode plate 160 having a positive electrode active material layer 163 on the surface (first surface 61b and second surface 61c) of the positive electrode current collector foil 61 is manufactured. Step T1 is different from step S1 of the embodiment only in that the hydroxide particles 67 are not contained, and the rest is the same. Thereafter, in step T2 (electrode body manufacturing step), the positive electrode plate 160, the negative electrode plate 70, and the separator 80 are wound in the same manner as in step S2 of the embodiment to manufacture a wound electrode body 150 (see FIG. 7). Next, in step S3 (accommodating step), the wound electrode body 150 is accommodated inside the battery case 30 in the same manner as in step S3 of the embodiment to manufacture an assembled battery 101A (see FIG. 9).

[0079] Next, in step T4 (moisture content adjustment step), the moisture content (moisture content) of the positive electrode active material layer end portions 163f, 163g is set to 100 ppm or more, and the moisture content (moisture content) of the positive electrode active material layer central portion 163h is set to a state in which it is less than the moisture content of the positive electrode active material layer end portions 163f, 163g. The positive electrode active material layer end portions 163f, 163g are end portions that occupy 10% of the range of the positive electrode active material layer 163 in the width direction DW (i.e., the axial direction DX). The positive electrode active material layer central portion 163h is a portion located at the center of the positive electrode active material layer 163 in the width direction DW (i.e., the axial direction DX), and occupies 10% of the range of the positive electrode active material layer 163 in the width direction DW (see FIG. 10).

[0080] Specifically, first, the assembled battery 101A is heated and dried at a temperature of 110° C. for two hours. The lid 11 of the assembled battery 101A has a liquid injection hole (not shown). Therefore, by heating and drying the assembled battery 101A, at least a part of the moisture contained in the wound electrode body 150 evaporates to the outside through the liquid injection hole. This makes it possible to reduce the amount of moisture contained in the positive electrode active material layer 163 throughout the positive electrode active material layer 163. This heating and drying reduces the moisture content of the positive electrode active material layer 163 to less than 100 ppm. In particular, the moisture content of the positive electrode active material layer 163 becomes approximately the same value (specifically, 65 to 68 ppm) throughout the positive electrode active material layer 163.

[0081] Thereafter, the assembled battery 101A is left for a predetermined time (e.g., 30 minutes) in an environment of 25°C and 25% RH to absorb moisture into the positive electrode active material layer ends 163f, 163g, and the moisture content of the positive electrode active material layer ends 163f, 163g is set to 100 ppm or more. Specifically, the assembled battery 101A is stored for a predetermined time in a thermo-hygrostat maintained at a temperature of 25°C and a humidity of 25% RH. As a result, moisture enters the assembled battery 101A through the liquid injection hole, and the moisture penetrates into the wound electrode body 150 from both ends in the axial direction DX of the wound electrode body 150. Therefore, the moisture content of the positive electrode active material layer center portion 163h is less likely to increase than that of the positive electrode active material layer ends 163f, 163g. Therefore, the moisture content of the positive electrode active material layer center portion is less than that of the positive electrode active material layer ends. Therefore, the moisture content of the positive electrode active material layer ends 163f, 163g becomes 100 ppm or more, and the moisture content of the positive electrode active material layer center portion 163h becomes lower than the moisture content of the positive electrode active material layer ends 163f, 163g.

[0082] Next, in step T5 (pouring step), similarly to step S4 of the embodiment, nonaqueous electrolyte 90 is poured into the interior of the assembled battery 101A to produce the injected battery 101B (see FIG. 9). However, in this modified embodiment, in the previous step T4, the wound electrode body 150 of the assembled battery 101A is made to satisfy the following two conditions (d) and (e). (d) The moisture content of the positive electrode active material layer ends 163f, 163g present on the surfaces of the current collector foil ends 61f, 61g of the positive electrode laminated portion 160b of the positive electrode active material layer 163 is 100 ppm or more. (e) The moisture content of the positive electrode active material layer center portion 163h present on the surfaces of the current collector foil center portion 61h of the positive electrode laminated portion 160b of the positive electrode active material layer 163 is less than the moisture content of the positive electrode active material layer ends 163f, 163g. Therefore, in step T5 (pouring step), the nonaqueous electrolyte 90 can be poured into the battery case 30 housing the wound electrode assembly 150 that satisfies the above two conditions (d) and (e).

[0083] Next, in step T6 (initial charging step), similarly to step S5 in the embodiment, initial charging is performed on the battery 1B for which electrolyte injection is complete. This activates the battery 101B to become the battery 101. After that, the battery 101 that has completed the initial charging is inspected, and the battery 101 is completed and ready for shipment.

[0084] In this modified embodiment, in step T5 (pouring step), the nonaqueous electrolyte 90 is poured into the battery case 30 housing the wound electrode body 150 that satisfies the two conditions (d) and (e). This makes it possible to manufacture a battery 101 in which "the surface of the current collector foil ends 61f, 61g of the positive electrode laminate 160b has a larger amount of AlF3 per unit area than the surface of the current collector foil central portion 61h of the positive electrode laminate 160b." This is because the greater the moisture content of the positive electrode active material layer 163 when the pouring step is performed, the more easily a coating of AlF3 having high corrosion resistance is formed on the surface of the positive electrode current collector foil 61 during the period from when the nonaqueous electrolyte 90 is poured into the battery case 30 until the battery 101 is shipped. In particular, by performing the liquid injection step with the moisture content of the positive electrode active material layer 163 set to 100 ppm or more, a highly corrosion-resistant AlF3 coating is easily formed on the surface of the positive electrode current collector foil 61 during the period from when the nonaqueous electrolyte 90 is injected into the battery case 30 until the battery 101 is shipped. In detail, the AlF3 coating formation reaction is promoted in the initial charging step, and the corrosion resistance of the surface of the positive electrode current collector foil 61 is increased. Therefore, according to the manufacturing method of this modified embodiment, it is possible to manufacture a battery 101 in which "Al elution from the surface of the positive electrode current collector foil 61 when a high load current is applied in the early stages of use" is reduced.

[0085] In the manufacturing method of this modified embodiment, a highly corrosion-resistant AlF3 coating is formed on the surface of the positive current collector foil 61 by a series of reactions (f) to (g) below. The surface of the positive current collector foil that is subjected to the positive plate fabrication step is coated with an Al2O3 coating, which is an oxide coating. Therefore, the surface of the positive current collector foil 61 included in the wound electrode body 150 that is subjected to the liquid injection step is also coated with an Al2O3 coating. (f) After the non-aqueous electrolyte 90 is injected into the battery case 30 in the electrolyte injection step, the H2O contained in the positive electrode plate 160 in the battery case 30 reacts with the LiPF6 in the non-aqueous electrolyte 90 to generate HF. LiPF6 + H2O → LiF + POF3 + 2HF (Equation 9) (g) The generated HF reacts with the Al2O3 coating on the surface of the positive current collector foil 61, generating an AlF3 coating on the surface of the positive current collector foil 61. Al2O3 + 6HF → 2AlF3 + 3H2O (Equation 10)

[0086] <Variations 1 to 3> In the first to third modified examples, the time (hereinafter, also referred to as the moisture absorption time) for leaving the assembled battery 101A in an environment of 25°C and 25% RH in step T4 (moisture content adjustment step) was varied to vary the moisture content of the positive electrode active material layer end portions 163f, 163g. As a result, the assembled batteries 101A of the first to third modified examples to be subjected to step T5 (liquid injection step) had different moisture contents of the positive electrode active material layer end portions 163f, 163g. The batteries 101 of the first to third modified examples were otherwise similarly produced. The moisture content of the positive electrode active material layer 163 of each modified example was measured by a known Karl Fischer moisture meter.

[0087] Specifically, in Modifications 1 to 3, the time for which the assembled battery 101A is left in an environment of 25°C and 25% RH (referred to as the moisture absorption time in Table 2) is 5 minutes, 30 minutes, and 120 minutes, respectively, for Modifications 1 to 3 (see Table 2). This causes the moisture content of the positive electrode active material layer ends 163f, 163g to differ between Modifications 1 to 3. Specifically, in Modifications 1 to 3, the moisture content of the positive electrode active material layer ends 163f, 163g in step T4 (moisture content adjustment step) is 110 ppm, 230 ppm, and 295 ppm, respectively, for Modifications 1 to 3 (see Table 2).

[0088] [Table 2]

[0089] <Comparative Example 2> In Comparative Example 2, in Step T4 (moisture content adjustment step), the assembled battery 101A was simply heated and dried at a temperature of 110°C for 2 hours, and then, without leaving the assembled battery 101A in an environment of 25°C and 25% RH, Step T5 (liquid injection step) was performed. In Comparative Example 2, in Step T4, the moisture content of the positive electrode active material layer ends 163f, 163g was set to 68 ppm (see Table 2). The battery of Comparative Example 2 was produced in the same manner as in Modification Example 1 except for Step T4.

[0090] <Investigation of the AlF3 coating on the positive electrode current collector foil> Next, for the batteries of Modifications 1 to 3 and Comparative Example 2, the AlF3 coating on the surface of the positive electrode current collector foil 61 was investigated in the same manner as in Example 1. Note that all of the batteries investigated were unused batteries that were completed and ready for shipment.

[0091] In Comparative Example 2, the surfaces of the current collecting foil ends 61f, 61g of the positive electrode laminate 160b had the same value of (F / Al) as the surface of the current collecting foil central portion 61h of the positive electrode laminate 160b. On the other hand, in Modifications 1 to 3, the surfaces of the current collecting foil ends 61f, 61g of the positive electrode laminate 160b had a larger value of (F / Al) than the surface of the current collecting foil central portion 61h of the positive electrode laminate 160b. Therefore, it can be said that the surfaces of the current collecting foil ends 61f, 61g of the positive electrode laminate 160b have a larger amount of AlF3 per unit area and a thicker coating of AlF3 than the surface of the current collecting foil central portion 61h of the positive electrode laminate 160b.

[0092] More specifically, in Modifications 1 to 3, the (F / Al) values ​​at the current collector foil ends 61f, 61g of the positive electrode laminate 160b were larger than in Comparative Example 2. From these results, it can be said that by injecting nonaqueous electrolyte 90 into battery case 30 housing wound electrode body 50 in which the moisture content of positive electrode active material layer ends 163f, 163g is 100 ppm or more in the liquid injection step (step T5), the formation of an AlF3 coating is then promoted on the surface of current collector foil ends 61f, 61g of positive electrode laminate 160b, and the corrosion resistance of the surface of current collector foil ends 61f, 61g of positive electrode laminate 160b can be improved.

[0093] <High-load current test> Next, a high-load current test was performed on the batteries of the modified examples 1 to 3 and the comparative example 2 in the same manner as in Example 1. Note that all the batteries used in this test were batteries that were completed and ready to be shipped, and were unused products (i.e., new products). Therefore, for all the batteries used in this test, the high-load current applied in this test was the high-load current applied in the early stages of use. In this test, similar to Example 1, each battery was charged and discharged 20 times, and then the presence or absence of Al elution from the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 was investigated. The presence or absence of Al elution was determined by the presence or absence of pitting corrosion in the positive electrode current collector foil 61 in the same manner as in Example 1. The results are shown in Table 2.

[0094] As shown in Table 2, in the first to third modifications, the evaluation of Al pitting corrosion was ◯, and no pitting corrosion was present on the first surface 61b and the second surface 61c of the positive current collector foil 61. From this result, it can be said that in the battery 101 of the first to third modifications, when a high load current was applied in the early stage of use, it was possible to prevent Al elution from the first surface 61b and the second surface 61c of the positive current collector foil 61. On the other hand, in the second comparative example, the evaluation of Al pitting corrosion was ×, and many pitting corrosion was present on the first surface 61b and the second surface 61c of the positive current collector foil 61. Specifically, many pitting corrosion was present on the current collector foil ends 61f and 61g of the positive laminated portion 160b. Therefore, it can be said that the battery of the second comparative example is prone to Al elution from the first surface 61b and the second surface 61c of the positive current collector foil 61 when a high load current was applied in the early stage of use.

[0095] <Discharge capacity measurement test> Further, the discharge capacity was measured for the batteries of Modifications 1 to 3 and Comparative Example 2 in the same manner as in Example 1. The results are shown in Table 2. As indicated by circles in Table 2, the batteries of Modifications 1 and 2 and Comparative Example 2 were able to obtain sufficient discharge capacity. Specifically, the discharge capacity of the battery of Comparative Example 1 was the largest, and the discharge capacity decreased as the amount of moisture in the positive electrode active material layer ends 163f, 163g during the liquid injection step was increased. In detail, the discharge capacity of the batteries of Modifications 1 and 2 was smaller than that of the battery of Comparative Example 1, but the amount of decrease was small.

[0096] On the other hand, as indicated by △ marks in Table 2, the discharge capacity of the battery of Modification 3 was smaller than that of the battery of Comparative Example 2, and the amount of decrease was larger than those of the lithium ion secondary batteries of Modifications 1 and 2. From the above results, it was found that the greater the amount of moisture in the positive electrode active material layer ends 163f, 163g during the liquid injection step, the smaller the discharge capacity of the battery, and that if the amount of moisture was 290 ppm or more, the decrease in the discharge capacity of the battery became greater.

[0097] From the above results, it can be said that it is more preferable that the moisture content of the positive electrode active material layer ends 163f, 163g during the liquid injection step is within a range of 100 ppm or more and less than 290 ppm, because this can reduce "Al elution from the surface of the positive electrode current collector foil 61 when a high load current is applied in the early stage of use of the battery" and also suppress a decrease in the discharge capacity of the battery.

[0098] In the first to third modified examples, the amount of moisture in the positive electrode active material layer central portion 163h during the liquid injection step is set to be less than the amount of moisture in the positive electrode active material layer ends 163f, 163g (see Table 2). This makes it possible to reduce the amount of decrease in the discharge capacity of the lithium ion secondary battery compared to when the amount of moisture in the positive electrode active material layer central portion 163h during the liquid injection step is set to be equal to the amount of moisture in the positive electrode active material layer ends 163f, 163g.

[0099] Although the present invention has been described above with reference to embodiments and modified forms, it goes without saying that the present invention is not limited to the above-described embodiments and can be modified as appropriate without departing from the spirit of the present invention. [Explanation of symbols]

[0100] 1,101 Lithium-ion secondary batteries 1B,101B Filled battery 30 Battery case 50,150 wound electrode body 60,160 Positive plate 60b, 160b Positive electrode laminated part 61 Positive electrode current collector foil 61f, 61g Current collector end of positive electrode laminate 61h Center of current collector foil of positive electrode laminate 63,163 Cathode active material layer 63f,63g,163f,163g Positive electrode active material layer end 67 Hydroxide particles 70 Negative plate 80 Separator 90 Nonaqueous electrolyte DX axis direction

Claims

1. A wound electrode assembly in which a strip-shaped positive electrode plate and a strip-shaped negative electrode plate are wound with a strip-shaped separator interposed therebetween; and LiPF 6 and a battery case that accommodates the non-aqueous electrolyte solution, The positive electrode plate includes a positive electrode current collector foil made of aluminum foil and a positive electrode active material layer laminated on a surface of the positive electrode current collector foil, a portion of the positive electrode plate where the positive electrode active material layer is laminated on the surface of the positive electrode current collector foil is defined as a positive electrode laminated portion; a portion of the positive electrode current collector foil included in the positive electrode laminated portion, the portion occupying at least 10% of a range from both ends in the axial direction of the wound electrode body, is defined as a current collector foil end portion of the positive electrode laminated portion, If a portion of the positive electrode current collector foil included in the positive electrode laminate portion that is located at the center in the axial direction of the wound electrode body is defined as a current collector foil center portion of the positive electrode laminate portion, The surface of the end portion of the current collecting foil of the positive electrode laminate has a larger amount of AlF per unit area than the surface of the central portion of the current collecting foil of the positive electrode laminate. 3 A large amount of Lithium-ion secondary battery.

2. A method for producing the lithium ion secondary battery according to claim 1, comprising the steps of: a positive electrode plate fabrication step of fabricating the positive electrode plate having the positive electrode active material layer on the surface of the positive electrode current collector foil; an electrode assembly fabrication step of fabricating the wound electrode assembly by winding the positive electrode plate and the negative electrode plate with the separator interposed therebetween; a housing step of housing the wound electrode body inside the battery case; a liquid injection step of injecting the nonaqueous electrolyte into the battery case containing the wound electrode body to prepare a liquid injection-completed battery; and an initial charging step of initially charging the battery after the electrolyte injection is completed, In the positive electrode plate preparation step, hydroxide particles are contained only in the positive electrode active material layer end portion that is present on the surface of the current collector foil end portion of the positive electrode laminate portion. A method for manufacturing a lithium-ion secondary battery.

3. A method for producing the lithium ion secondary battery according to claim 2, comprising the steps of: The hydroxide particles are LiOH particles. A method for manufacturing a lithium-ion secondary battery.

4. A method for producing the lithium ion secondary battery according to claim 1, comprising the steps of: a positive electrode plate fabrication step of fabricating the positive electrode plate having the positive electrode active material layer on the surface of the positive electrode current collector foil; an electrode assembly fabrication step of fabricating the wound electrode assembly by winding the positive electrode plate and the negative electrode plate with the separator interposed therebetween; a housing step of housing the wound electrode body inside the battery case; a liquid injection step of injecting the nonaqueous electrolyte into the battery case containing the wound electrode body to prepare a liquid injection-completed battery; and an initial charging step of initially charging the battery after the electrolyte injection is completed, The liquid injection step includes: The nonaqueous electrolyte is injected into the inside of the battery case that houses the wound electrode body, in which the moisture content of the positive electrode active material layer end portion present on the surface of the current collector foil end portion of the positive electrode laminated portion of the positive electrode active material layer is 100 ppm or more, and the moisture content of the positive electrode active material layer central portion present on the surface of the current collector foil central portion of the positive electrode laminated portion of the positive electrode active material layer is less than the moisture content of the positive electrode active material layer end portion. A method for manufacturing a lithium-ion secondary battery.

5. A method for producing the lithium ion secondary battery according to claim 4, comprising the steps of: Between the containing step and the liquid pouring step, The moisture content of the end portion of the positive electrode active material layer is adjusted to a value within a range of 100 ppm or more and less than 290 ppm, and the moisture content of the central portion of the positive electrode active material layer is adjusted to a value less than the moisture content of the end portion of the positive electrode active material layer. A method for manufacturing a lithium-ion secondary battery.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery and collector for the secondary battery

    JP2014120331A

  • Lithium ion secondary battery and manufacturing method of the same

    JP2015099725A

  • Nonaqueous electrolyte secondary battery

    JP2015207419A

  • Electrochemical cell, electrolyte suitable for filling an electrochemical cell, method for manufacturing an electrochemical cell, and method for operating an electrochemical cell

    JP2017528880A

  • Nonaqueous secondary battery

    JP2018060689A